Taxes, banks and financial stability - Reint E. Gropp (Goethe University Frankfurt, SAFE - Sustainable Architecture for Finance in Europe, 2013)
In this note, a new concept for a European deposit guarantee scheme is proposed, which takes account of the strong political reservations against a mutualization of the liability for bank deposits. The three-stage model for deposit insurance outlined in the text builds on existing national deposit guarantee schemes, offering loss compensation on a European level and at the same time preventing excessive risk and moral hazard taking by individual banks.
urn:nbn:de:hebis:30:3-314064
Keywords: 330; bank risk; banking union; deposit insurance